The Implementation of Bipartite Graph To Minimize Crossing Number Problem of Crossroads in Manado - Nazareth, Timboeleng Axellica; Montolalu, Chriestie E.J.C; Pinontoan, Benny (Universitas Sam Ratulangi, 2019)
The Implementation Of Bipartite Graph To Minimize Crossing Number Problem OfÂ Crossroads In Manado. Supervised by BENNY PINONTAN as main supervisor and CHRIESTIE E. J. C. MONTOLALU as co-supervisor. In general, the crossroads are the meeting points of two-way roads from four different places. This causes cross direction at that point. There are various methods that can be used to minimize the crossing number problem crossroad, for example graph theory. The ability of graph theory can later help describe crossroads in Manado into graph, with nodes and lines. In this case, the crossing number problems will solve by bipartite graph. Bipartite graph is a graph that does not have an odd cycle, and can be partitioned into two parts of a set of vertices. Based on results of this research, the appropriate form of the bipartite graph is and Â in two different form. First, with an isolated vertex, and second, without isolated vertex. In the case of crossroads, Bipartite graph turns out to be one method that is very suitable and helps determine the crossing number and its solution quickly.